Patients’ perceptions of use, needs, and preferences related to a telemedicine solution for HIV care in a Norwegian outpatient clinic: a qualitative study - Hege Mari Johnsen; Anita Øgård-Repål; Santiago Gil Martinez; Kim Fangen; Kristin Bårdsen Aas; Ellen Margrete Iveland Ersfjord (BMC Health Services Research, 2024)
Abstract Background Telemedicine in outpatient services for people living with human immunodeficiency virus (PLHIV) was scaled up during the COVID-19 pandemic as services transitioned to remote care. Many studies have reported on the challenges and advantages of telemedicine care during the pandemic. However, there is limited research on the provision of telemedicine human immunodeficiency virus (HIV) care beyond the COVID-19 pandemic, which entails different telemedicine components and focuses on ways to improve the telemedicine experience for patients. This study aimed to explore PLHIV’s perceptions of use, needs, and preferences related to a telemedicine solution for HIV care in an outpatient clinic in Norway. The telemedicine solution included a pre-consultation questionnaire, asynchronous digital messages, and video consultation. Methods Qualitative interviews were conducted with 12 PLHIV. The interviews were analysed using thematic analysis. Results We identified four main themes that covered the participants’ perceptions, needs, and preferences: (1) perceived usability, (2) maintaining confidentiality, (3) accommodating personal preferences, and (4) perceived usefulness. Some participants had difficulty logging into the telemedicine solution. Other participants suggested additional functionalities, such as picture sharing and access to test result. Telemedicine care enabled the avoidance of stigmatising clinic experiences, although a few participants reported concerns about confidentiality and data security. Accommodating personal preferences and needs in terms of the type of consultations (in-person or video) and frequency of visits was essential to the participants. With telemedicine care, participants felt more in control of their own lives, perceiving that it increased their perceived quality of life and saved them both time and money for travelling to the clinic. Conclusions Our study identified several specific needs and preferences related to the assessed technical solution and the provision of current and future telemedicine care services. Nevertheless, the telemedicine solution was perceived as a usable, flexible, and person-centred approach to HIV care, contributing to accommodating the participants’ personal preferences. However, healthcare professionals need to ensure that individual requirements and preferences are consistent with evidence-based follow-up and supported by person-centred care. Thus, the practice of shared decision making is important in telemedicine care.